Gefäßkeramik als Mittel zur Datierung und zur Bestimmung der Nutzungsdauer eines Siedlungsbefundes am Beispiel des frühmittelalterlichen Burgwalls von Lubin - Marek Dworaczyk (Fasciculi Archaeologiae Historicae)
Vessel pottery discovered in the course of research in the early medieval stronghold in Lubin in Wolin Island (Western Pomerania) is remarkable for a strong fragmentation and deformation. However, various methods which were applied to discuss it, including a size classification of vessel shards and a qualitative-quantitative analysis, allowed to properly assess these shards. On the one hand, these criteria allowed to establish the chronology of the vessel assemblage and thus to identify the settlement dynamics of this feature. On the other hand, it became possible to explain reasons behind this considerable fragmentation of the shards. It seems that it resulted from the intensity of development of the stronghold.